2015
DOI: 10.1007/s11295-015-0907-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting genome variation to improve next-generation sequencing data analysis and genome editing efficiency in Populus tremula × alba 717-1B4

Abstract: Populus species are widely distributed across the Northern Hemisphere. The genetic diversity makes the genus an ideal study system for traits of ecological or agronomic significance. However, sequence variation between the genome-sequenced Populus trichocarpa Nisqually-1 and many other Populus species and hybrids poses significant challenges for research that employs sequence-sensitive approaches, such as next-generation sequencing and sitespecific genome editing. Using the routinely transformed genotype Popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Approximately 12–32 million (M) paired-end 75-bp reads were obtained per sample. To identify T-DNA insertion sites, individual reads were mapped to the vector as well as the Populus tremula x alba custom genome v1.1 45 using BLAT. Custom Perl scripts were used to filter for paired reads flanking an insertion site, e .…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 12–32 million (M) paired-end 75-bp reads were obtained per sample. To identify T-DNA insertion sites, individual reads were mapped to the vector as well as the Populus tremula x alba custom genome v1.1 45 using BLAT. Custom Perl scripts were used to filter for paired reads flanking an insertion site, e .…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequences for all genes used in this study are given in Supporting Information Table S1. WT from 35°C, SRP146326 and SRP146339 for transgenic line F10 from 27°C, and SRP146340, SRP146325, and SRP146322 for F10 from 35°C. Sequence reads were quality checked and mapped onto a variant-substituted P. tremula 9 alba genome (sP-ta717) v1.1 as described (Xue et al, 2015) using Tophat2 v2.0.12 (Kim et al, 2013). Transcript abundance was estimated by HTSeq (Anders et al, 2015) and differential expression performed using DESeq2 (Love et al, 2014).…”
Section: Rna Isolation Complementary Dna Synthesis and Quantitativementioning
confidence: 99%
“…Gray poplar is a hybrid species derived from a cross between silver poplar (Populus alba) and quaking aspen (Populus tremula) and BLAST searches with the different P. trichocarpa AAAD genes as query and the genomes of P. 3 canescens, P. alba, and P. tremula (http://aspendb. uga.edu/index.php/databases/spta-717-genome; Xue et al, 2015;Zhou et al, 2015) as templates revealed that all three species possess putative AADC1, AADC2, and AAS1 orthologs (Supplemental Fig. S8).…”
Section: Rnai-mediated Downregulation Of Ptaadc1 In Populus 3 Canescementioning
confidence: 99%